Electronic toilet / Wan Mohammad Faisal Wan Mohammed, Zulhusni Roslee and Puteri Izyan Izzati Hassan - Wan Mohammed, Wan Mohammad Faisal; Roslee, Zulhusni; Hassan, Puteri Izyan Izzati (2013)
This ‘Electronic Toilet’ has its own function to control the cleanliness inside the toilet especially public toilet. Some of the circuit that involve are motion detector circuit, water level circuit and timer circuit. Other stuff that is used for this project is solenoid. In this circuit, motion detector circuit is the main circuit for this project. Its function is to sense movement inside the toilet to activate the whole circuit so that all of the circuit would functional. Moreover, water level circuit is used to detect the level of water when it reaches the level and the door will automatically open. Lastly, timer is used to control the machine so that it would stop and start the machine. In this project, timer is connected to the sensor. So that when the sensor detects motion, light and fan would switch ON. This timer circuit would make the light and fan to switch ON much longer within the given time. While solenoid is use for the door, it would act as magnet. So that when the door is not open it would close.